Integrating Gender and Intersectionality in LIS Education: A Narrative Review of Innovative Curricular Approaches - Boté-Vericad, Juan-José; Mandl, Thomas; Petr Balog, Kornelija; Cupar, Drahomira; Dombrovská, Michaela; Dreisiebner, Stefan; Khattab, Džejla (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2026)
Gender and intersectionality remain underrepresented in Library and Information Science (LIS) education, where related content is frequently peripheral, elective in nature, or left to individual staff initiative. This paper presents a narrative review of international studies on gender inclusion in LIS curricula and pedagogy. We reviewed a final sample of 42 sources and synthesised them thematically. The analysis is guided by intersectionality, feminist pedagogy, and a critical curriculum stance, foregrounding how power operates through what curricula include, omit, and assess. Across contexts, literature identifies persistent structural gaps: explicit gender or diversity learning outcomes are rare in core modules; inclusive‑language commitments are uneven; teaching materials and bibliographies often reproduce androcentric and Eurocentric canons; and evaluation mechanisms remain limited. Inclusion is also commonly confined to electives or isolated staff initiatives. Faculty frequently report limited training, time, and institutional support to teach gender‑related content with confidence, and studies highlight a disconnect between equity scholarship and its translation into classroom practice, as well as diluted or performative uses of intersectionality. Addressing two research questions, the review examines (1) the extent and forms of gender and intersectionality integration in LIS curriculum design, pedagogy, and institutional mechanisms, and (2) the barriers, enablers, and promising approaches for achieving structural embedding. Participatory action research, co‑created syllabi, and community‑linked learning projects emerge as promising but unevenly implemented strategies. The review recommends embedding gender through assessed learning outcomes, resourced staff development, and periodic curriculum audits. Sustainable change requires shared institutional accountability and reflexive, justice‑oriented pedagogical practice in LIS education.